(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Laboratory experiments were conducted to study the effect of temperature on the effectiveness of the oil formulation i.e., neem oil, eucalyptus oil, and canola oil against rice weevil, Sitophilus oryzae (Linn.) on stored maize seeds during 2021-22.The treated maize seeds were maintained at different temperature ranges within BOD incubators, recording percent adult mortality and rice weevil population growth.The results showed that 3 days after treatment (3DAT) neem and eucalyptus oils were most effective against S. oryzae with 65.33 and 63.97 percent mortality respectively at 25°C which reduced to 63.33 and 62.41 percent respectively at 36°C. The Cannola oil showed alike results at 25°C to 36 °C. Seven and fourteen days after treatment, neem and eucalyptus oil showed a reduction in percent mortality with an increase in temperature whereas percent mortality in cannola oil-treated seeds at different temperatures remains unaffected. In case of population growth up to 3 months of storage, neem and eucalyptus oil showed an increase in the population of S. oryzae as the temperature increased but canola oil remains unaffected while after 6 months all tested oil formulations indicated a positive correlation with temperature.